A new Triodopsis juxtidens subspecies (Gastropoda: Pulmonata) from West Virginia, U.S.A. - Hotopp, Kenneth P. (Zootaxa, 2015)
The Appalachian Mountains of North America hold a unique diversity of land snails, including those within the family Polygyridae genus Triodopsis. West Virginia has ten or more representatives of the genus (Hubricht, 1985), displaying variations upon the conchological theme of a depressed heliciform shape with a reflected peristome bearing three lamellae. However, it remains unclear whether all of the recognized variants on this theme represent species as commonly defined. In the case of the Triodopsis juxtidens (Pilsbry, 1894) subgroup as defined by Emberton (1988)—T. juxtidens, T. discoidea (Pilsbry, 1904), T. neglecta (Pilsbry, 1899), and T. pendula Hubricht, 1952—no penial morphology or allozyme differences are known (Emberton, 1988). Conversely, mitochondrial DNA analysis that included five T. juxtidens specimens suggests this putative species is not monophyletic (Perez et al., 2014). Rampant variation in shell morphology among Triodopsis species creates further taxonomic and identification challenges. Without additional supporting evidence for species-level differences, such as anatomical and genetic analyses, a conservative taxonomic approach is to recognize regionally distinct forms as subspecies. A unique form from the upper Bluestone River watershed is described here as Triodopsis juxtidens robinae subsp. nov.